Rogue Wave Observations Off the US West Coast - Burkard Baschek; Jennifer Imai (The Oceanography Society, 2011)
Rogue waves can cause significant damage to vessels and offshore structures and are linked to the loss of hundreds of lives at sea. They represent extreme statistical events with wave heights exceeding twice the significant wave height. The authors investigated a wave buoy data set collected off the US West Coast with 7,157 rogue waves observed over a total of 80 years. It yields comprehensive statistics regarding the likelihood of rogue wave occurrence in the open ocean, coastal ocean, and shallow water. The highest recorded rogue wave had a trough-to-crest height of 18.95 m. The average likelihood of occurrence is 63 per year in coastal waters and 101 per year in the open ocean. An extrapolation to conditions in the world ocean yields an average likelihood of encountering rogue waves along the main shipping routes in the North Atlantic of 0.8–1.2% per day for rogue waves exceeding 11 m in height. The results can be used to test rogue wave forecasting models and will help to improve the forecasting of hazardous ocean conditions.